Co-occurrence of Fatigue and Depression in People With Multiple Sclerosis: A Mini-Review - Tarasiuk, Joanna; Kapica-Topczewska, Katarzyna; Czarnowska, Agata; Chorąży, Monika; Kochanowicz, Jan; Kułakowska, Alina (Frontiers in Neurology, 2022)
Fatigue and depression are common conditions diagnosed in people with multiple sclerosis (MS). Fatigue defined as subjective lack of physical and/or mental energy is present in 35–97% of people with MS, who classify it as one of the most serious symptoms interfering with daily activities and influencing the quality of life. Depression is diagnosed in about 50% of people with MS. Since fatigue and depression frequently coexists, it may be quite hard to differentiate them. Primary fatigue and primary depression in MS are caused by inflammatory, oxidative/nitrosative, and neurodegenerative processes leading to demyelination, axonal damage, and brain atrophy. In people with MS and comorbid fatigue and/or depression there is reported increased serum and cerebrospinal fluid concentration of inflammatory mediators such as tumor necrosis factor, interleukins (IL-1a, IL-1b, IL-6), interferon γ and neopterin. Moreover, the brain atrophy of prefrontal, frontal, parietotemporal regions, thalamus, and basal ganglia was observed in people with MS with fatigue and/or depression. The secondary fatigue and secondary depression in people with MS may be caused by emotional factors, sleep disorders, pain, the coexistence of other diseases, and the use of medications. In some studies, the use of disease-modifying therapies positively influenced fatigue, probably by reducing the inflammatory response, which proves that fatigue and depression are closely related to immunological factors. In this mini-review, the pathogenesis, methods of evaluation and differentiation, and possible therapies for fatigue and depression in MS are discussed.